Black womanhood : images, icons, and ideologies of the African body - Thompson, Barbara; Hood Musem of Art, Hanover (New Hampshire); Davis Museum and Cultural Center, Wellesley College, Wellesley (Massachusetts); San Diego Museum of Contemporary Art, San Diego (Hanover : Hood Museum of Art, Dartmouth College Hanover, 2008)
Douglas Camp, Sokari ; Mntambo, Nandipha ; Siopis, Penny ; Sulter, Maud ; Odundo, Magdalena ; Dimma Poulsen, Etiyé ; Guebehi, Emile ; Cox, Renée ; Musa, Hassan ; Mutu, Wangechi ; Saar, Alison ; Sidibé, Malick ; Essamba, Angèle Etoundi ; Ingridmwangiroberthutter ; Campos-Pons, Maria Magdalena ; Scott, Joyce ; Walker, Kara Elizabeth ; Sheikh, Fazal ; Muholi, Zanele ; Searle, Berni ; Essaydi, Lalla ; Weems, Carrie Mae
Biog. p. 352-358, biog. auteurs p. 359-360, bibliog. p. 361-368
Publication on the occasion of the exhibition 'Black womenhood : images, icons, and ideologies of the African body' in the Hood Musem of Art in Hanover (New Hampshire), 01.04.2008 - 10.08.2008 and at the Davis Museum and Cultural Center, Wellesley College in Wellesley (Massachusetts), 10.09.2008 - 10.12.2008 and at the San Diego Museum of Contemporary Art in San Diego, 31.01.2009 - 26.04.2009
boek